Impact of Numerical Abilities and Socio-Economic Backgrounds on Entrepreneurial Intentions of Business Education Students in Nigeria - Olorode, Jide John (International Journal of Research in Interdisciplinary Studies, 2025)
Recognizing entrepreneurship as a vital driver of economic growth and job creation, the research addresses why many aspiring entrepreneurs still face barriers despite government initiatives and business education programs. This study explores how numerical abilities and socio-economic backgrounds influence the entrepreneurial intentions of business education students in Nigeria. Using a quantitative, cross-sectional survey, data were collected from 300 business education students and 12 lecturers across three tertiary institutions in South-West Nigeria. The study assessed students’ proficiency in numeracy, their socio-economic backgrounds, and their intentions to pursue entrepreneurship. Results revealed that students generally exhibited low numeracy skills, particularly in applied business mathematics and financial literacy, with only about 41% demonstrating adequate financial knowledge. Socio-economic background was found to be a much stronger predictor of entrepreneurial intentions than numerical ability; students from wealthier families and with more educated parents were significantly more likely to express entrepreneurial ambitions. The findings suggest that while improving numeracy and financial literacy is important, addressing socio-economic disparities is even more crucial for fostering entrepreneurial ambition among students. The study recommends targeted interventions, such as financial support and numeracy mentoring for students from less privileged backgrounds, as well as curriculum reforms to enhance practical business mathematics.